Numerical study on scroll vortex intake with non-uniform approach flow conditions - Wang, Yiran (2024)
Scroll vortex dropshafts have been adopted as an effective tool to convey flow from higher to lower elevations in drainage systems. To ensure the reliability of these dropshafts, the approach channel would normally need to achieve uniform inflow conditions through a minimum channel length requirement. In dense urbanized cities, however, these conditions are occasionally unattainable due to land space constraint. Hence, further investigation is needed to examine the effect of non-uniform inflow conditions on the flow regimes and hydraulic performance of scroll vortex dropshafts. This study aims to quantify the effect of various non-uniform inflow factors on the non-dimensional head-discharge relationship and minimum air core size of the scroll vortex dropshaft by means of computational fluid dynamics simulations. Three-dimensional numerical models with different approach channel lengths are first constructed, and simulations in uniform inflow conditions are then performed and validated by experiment data. Subsequently, simulations with non-uniform inflow conditions are carried out with varying discharges as well as cross-sectional velocity distributions. The results showed that the effect on the performance of the dropshaft depends more on the distribution profile than its peakiness. A higher water level at the entrance and dilated minimum air core size in the dropshaft are typically observed for biased inflow conditions with inward velocity distributions toward the vortex chamber center, while outward distributions toward the outer wall of the vortex chamber lead to an opposite effect. A shorter approach channel would aggravate the disparity magnitude as expected. Finally, regression equations are established based on the simulation results to enable the assessment on the effect of non-uniform inflow conditions in the design stage.